Sibling sex, but not androgens, shapes phenotypes in perinatal common marmosets (Callithrix jacchus) - Frye, Brett M. (Sci Rep, 2019)
When offspring share a womb, interactions among fetuses can impart lasting impressions on phenotypic outcomes. Such intrauterine interactions often are mediated by sex steroids (estrogens and androgens) produced by the developing fetuses. In many mammals, intrauterine interactions between brothers and sisters lead to masculinization of females, which can induce fitness consequences. Many litter-bearing primates, though, seem to escape androgen-mediated litter effects, begging why? Here, we investigated how the sex composition (i.e., same- or mixed-sex) of litters influences perinatal outcomes in the common marmoset monkey (Callithrix jacchus), using a combination of physiological, morphological, and behavioural assays. We hypothesized that androgens from male fetuses would mediate developmental differences across litter types. We found that newborns (24–36 hours old) from same- and mixed-sex litters were indistinguishable by urinary androgen profiles, birth weights, morphometrics, and behaviour. However, monkeys born into same- and mixed-sex litters exhibited subtle morphological and neurobehavioral differences later in the perinatal period, independent of their androgen profiles. Our findings suggest that while androgens from male fetuses likely do not organize their siblings’ phenotypes, perinatal stimuli may initiate divergent developmental trajectories among siblings, which, in turn, promotes inter-individual variability within families.